Evidence-based verification of the possibilities of etio-pathogenetic diagnosis of psychosomatic pathology using the trance method of "root cause" #Reavisia - Катостровський, Oleg (Psychosomatic Medicine and General Practice, 2023)
The short report presents cases showing the possibilities of diagnosing the causes of the development of psychosomatic conditions and psychiatric pathology using the Reavisia "root cause" method - the author's approach of regressive trance.